Research of the heat of physical characteristics of fruit ossicles - N. A. Mironova (Известия высших учебных заведений: Проблемы энергетики)
Utilization of fruit seeds plays a special role, since they are a valuable raw material for the oil and fat industry, at the enterprises of which the complex processing of seeds is carried out: oil is obtained from kernels, crumbs and powder are obtained from shells. Before placing the seeds in the oil and fat enterprises, they must be cleaned of impurities and dried, since the seeds extracted from the fruits have an increased humidity of 25-60% and contain a significant amount of impurities in the form of pulp and squeezes. However, due to the lack of specialized equipment for drying fruit seeds in canneries, their supply to the kernel oil plants is declining every year. In this case, tons of seeds are simply destroyed. Attempts to use existing industrial dryers proved to be ineffective, since they do not take into account the structural features of fruit seeds, and are also not very adapted to significant fluctuations in the moisture of raw seeds and the unevenness of their receipt on drying. The most appropriate method of drying fruit seeds is the use of infrared radiation and a vibro-boiling layer.